Formação de professores no contexto de grupos de pesquisa da área ambiental: saberes ambientais e identidade docente - SOUSA, Fernanda Rocha de (Universidade Federal do Pará, 2023)
This study had the guide question “How do research groups with an emphasis on environmental issues contribute to the constitution of environmental knowledge, professional identity and teacher training in the Amazonian scenario of Pará?” and, to answer this question, it aimed to understand in which terms the research groups in the environmental area collaborate for the constitution of environmental knowledge, for the delineation of the professional identity and the teachers training, especially in the Amazonian scenario of Pará. The study was based in the discussion of the postmodernity crisis using the references of Boaventura de Sousa Santos and Leff to understand the importance of this discussion for the teacher’s training, as well as Ciampa and Dubar to analyse the professionals identities of the teachers. Therefore, it was a qualitative research that used as a data collection technique the semi-structured interview and the content analysis, proposed by Bardin, in the treatment and analysis of the data. This thesis presents data obtained from a field research carried out by the Research Group on the Environment (Grupema), from the University of the State of Pará (UEPA) and by the Research Group on Environmental Education in the Amazon (Geamaz). Six teachers linked to both groups were the informers of this investigation. The text is organized in the form of five articles that aims to understand the contributions of research groups to the proposed discussion. The research showed that Grupema and Geamaz constituted an important base in the teachers training and in the constitution of the professional identities of the interviewees, insofar as they contribute to the professional development of the interviewees in terms of scientific initiation, initiation to teaching, scientific production and research experience with traditional communities, and for the personal and professional trajectory of these subjects; also constituting a link between researchers and groups and communities outside the university. As a potential for future researchs, it is important to expand the view on this discussion in order to understand the place these groups occupy within the university and to look for new ways of analyzing the contribution of these spaces to the various areas of teacher training.